Method for preparing battery-grade lithium fluoride by solid-phase method
The impurities in lithium chloride were removed by solid phase method, and high-purity battery-grade lithium fluoride was successfully prepared through rotary vaporization, vacuum drying and high-temperature reaction, which solved the problems of high impurities and insufficient purity of products in the prior art, and achieved simplification of the process and convenience of industrial production.
Patent Information
- Application Number
- CN202411831103.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing lithium fluoride production methods have problems such as high equipment cost, low reaction yield, low product main content, high moisture content and high impurity content, and it is difficult to achieve battery-grade purity and standards.
The solid phase method is used to remove impurities in lithium chloride by mixing the extractant, then rotate and vacuum drying, and finally react with ammonium hydrogen fluoride under an argon or nitrogen atmosphere to heat up and remove impurities to prepare battery-grade lithium fluoride.
It realizes the preparation of high-purity battery-grade lithium fluoride, the product has low impurity content, simple process operation, and easy industrial production.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium batteries, and in particular relates to a method for preparing battery-grade lithium fluoride by a solid phase method. Background Art
[0002] Against the backdrop of the rapid development of the battery industry, battery manufacturing technology is becoming the focus of attention of enterprises and scientific research institutions. Lithium batteries stand out among many battery technologies and become a hot topic of research due to their advantages such as high energy density, long life and no memory effect. As one of the key raw materials for lithium batteries, lithium fluoride is of great importance. Lithium fluoride (LiF) is a key inorganic fluoride that is a white powder at room temperature and is difficult to dissolve in water. It is widely used in the nuclear industry, enamel industry, optical glass manufacturing, preparation of lithium hexafluorophosphate, a raw material for lithium-ion battery electrolytes, and other fields. It is a very important lithium-based metal material.
[0003] Lithium fluoride production mainly includes two methods: neutralization method and double decomposition method. At present, industrial production mostly adopts neutralization method, which is to add solid lithium carbonate or lithium hydroxide to hydrogen fluoride solution to react and separate lithium fluoride, and then filter, dry, evaporate to dryness in platinum dish or lead dish to obtain. The lithium fluoride prepared by this production method is simple to operate, but has the disadvantages of high equipment cost, low reaction yield, low main content of product, high moisture content and high impurity content. The double decomposition method is to dissolve ammonium fluoride and lithium hydroxide or lithium carbonate in water respectively, and react by heating and stirring at the same time. In the reaction process, lithium fluoride can be separated out in solid form, and then the lithium fluoride product is prepared by steps such as filtering, washing and drying, but this method has the disadvantages of too much mother liquor discharge and too high impurity content in the product.
[0004] In the prior art, patent document CN115304084A provides a method for preparing nano lithium fluoride by solid phase reaction, under ultrasonic conditions, lithium hydroxide suspension and ammonium fluoride suspension are slowly mixed to react, by fully dispersing precursors in an organic solvent, and fully reacting in the form of slow mixing, ensuring full utilization of raw materials. Under the suspension system of organic solvent, ammonium fluoride and lithium hydroxide two kinds of raw materials react in the form of solid, increase the reaction energy barrier, suppress the growth of crystal grains, and improve the nucleation rate of crystal grains under the effect of ultrasonic radiation at the same time, and further improve the dispersion uniformity of reactants, and obtain nanometer-level lithium fluoride particles under the simultaneous effect of both. The lithium fluoride purity obtained by the above method is higher, but still does not reach the electronic grade level.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] In view of the shortcomings of the prior art, the object of the present invention is to provide a method for preparing battery-grade lithium fluoride by a solid phase process, which has simple process operation, does not produce additional water, and is convenient for industrial production.
[0007] In order to achieve the above object, the present invention adopts the following technical solution:
[0008] In a first aspect, the present invention provides a method for preparing battery-grade lithium fluoride by a solid phase process, comprising the following steps:
[0009] (1) Pour a mixed extractant obtained by mixing di(2-ethylhexyl) phosphate (P204) and sulfonated kerosene into a funnel, adjust the pH value, shake and separate the layers, remove the lower aqueous phase, and obtain an extract;
[0010] (2) pouring the lithium chloride solution into the extract obtained in step (1) to extract and remove impurities, and retaining the lower layer liquid;
[0011] (3) subjecting the lower layer liquid obtained in step (2) to rotary evaporation to obtain a rotary evaporation liquid;
[0012] (4) vacuum drying the rotary evaporation liquid obtained in step (3) to obtain crude lithium chloride;
[0013] (5) mixing the crude lithium chloride obtained in step (4) and ammonium bifluoride, and then reacting;
[0014] (6) Raise the temperature and remove impurities to obtain battery-grade lithium fluoride.
[0015] Preferably, in step (1), the volume ratio of di(2-ethylhexyl)phosphate to sulfonated kerosene is 2-8:2-8.
[0016] Preferably, in step (1), the pH value is adjusted to 10-12; a 5-10 wt % sodium hydroxide solution is used to adjust the pH value; and the oscillation time is 3-10 min.
[0017] Preferably, in step (2), the concentration of the lithium chloride solution is 10 to 30 wt%.
[0018] Preferably, in step (3), the rotary evaporation temperature is 70 to 90° C., the rotation speed is 50 to 70 rpm, and the vacuum degree is -0.05 to -0.1 MPa;
[0019] The concentration of the rotary evaporation liquid is 40-60wt%.
[0020] Preferably, in step (4), the vacuum drying temperature is 100 to 140° C., the drying time is 5 to 10 hours, and the vacuum degree is -0.05 to -0.1 MPa.
[0021] Preferably, in step (5), the molar ratio of crude lithium chloride to ammonium bifluoride is 1:1.2-1.5.
[0022] Preferably, in step (5), the reaction is carried out under an argon or nitrogen atmosphere, the reaction temperature is 160-180° C., and the reaction time is 3-5 h.
[0023] Preferably, in step (6), the temperature removal is carried out under an argon or nitrogen atmosphere at a temperature of 350 to 600° C. and a holding time of 3 to 5 hours.
[0024] In a second aspect, the present invention seeks to protect the battery-grade lithium fluoride prepared by the above method.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] 1. The present invention provides a method for preparing battery-grade lithium fluoride by a solid phase method. Impurities in lithium chloride can be effectively removed by a mixed extractant, and the obtained battery-grade lithium fluoride product has high purity.
[0027] 2. The present invention provides a method for preparing battery-grade lithium fluoride by a solid phase method, which adopts a dry method to synthesize lithium fluoride and introduces less impurities.
[0028] 3. The present invention provides a method for preparing battery-grade lithium fluoride by a solid phase method, which has simple synthesis and separation and purification processes, is easy to operate, and is convenient for industrial production. DETAILED DESCRIPTION
[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Unless otherwise specified, all commodities or reagents in the present invention were purchased through market channels.
[0031] The argon or nitrogen used are all high-purity, with a purity of ≥99.999%.
[0032] Example 1
[0033] Take industrial-grade lithium chloride raw material and set it aside; the content of the raw industrial-grade lithium chloride is 99.06%, sodium is 168ppm, magnesium is 22ppm, potassium is 167ppm, calcium is 70ppm, iron is 12ppm, and sulfate is 95ppm.
[0034] A method for preparing battery-grade lithium fluoride by a solid phase method comprises the following steps:
[0035] (1) Pour a mixed extractant obtained by mixing di(2-ethylhexyl) phosphate (P204) and sulfonated kerosene at a ratio of 20 mL:80 mL into a separatory funnel, then add 10 mL of a 10 wt% NaOH solution to the separatory funnel until the pH value is 11, then shake for 3 minutes, let stand and separate the lower aqueous phase to obtain an extract;
[0036] (2) Pour 423.9 g of 10% lithium chloride solution into the extract obtained in step (1) to extract and remove impurities, and retain the lower layer liquid;
[0037] (3) subjecting the lower layer liquid obtained in step (2) to rotary evaporation (rotary evaporation temperature: 70° C., rotation speed: 50 rpm, vacuum degree: −0.098 MPa) to obtain a 42% lithium chloride solution (i.e., rotary evaporation liquid);
[0038] (4) placing the rotary evaporation liquid obtained in step (3) into a vacuum drying oven for vacuum drying (vacuum temperature 100° C., time 5 h, vacuum degree -0.098 MPa) to obtain crude lithium chloride;
[0039] (5) mixing the crude lithium chloride obtained in step (4) and ammonium bifluoride in a molar ratio of 1:1.2, and reacting at 160° C. for 3 h under a 99.999% argon atmosphere;
[0040] (6) Finally, the temperature was raised to 350° C. in a 99.999% argon atmosphere for reaction for 3 h to obtain 24.92 g of the battery-grade lithium fluoride.
[0041] The product yield is 96.98%, and the measured product purity is 99.96%. The impurities sodium is 6ppm, magnesium is 4ppm, potassium is 5ppm, calcium is 2ppm, iron is 4ppm, and sulfate is 14ppm, which can meet the battery grade lithium fluoride standard.
[0042] Example 2
[0043] Take industrial-grade lithium chloride raw material and set it aside; the content of the raw industrial-grade lithium chloride is 99.11%, sodium is 155ppm, magnesium is 24ppm, potassium is 158ppm, calcium is 62ppm, iron is 14ppm, and sulfate is 82ppm.
[0044] A method for preparing battery-grade lithium fluoride by a solid phase method comprises the following steps:
[0045] (1) Pour a mixed extractant obtained by mixing di(2-ethylhexyl) phosphate (P204) and sulfonated kerosene at a ratio of 40 mL:60 mL into a separatory funnel, then add 5 mL of a 20 wt% NaOH solution to the separatory funnel until the pH value is 10, then shake for 5 minutes, let stand, separate and remove the lower aqueous phase to obtain an extract;
[0046] (2) Pour 211.95 g of 20% lithium chloride solution into the extract obtained in step (1) to extract and remove impurities, and retain the lower layer liquid;
[0047] (3) subjecting the lower layer liquid obtained in step (2) to rotary evaporation (rotary evaporation temperature 80° C., rotation speed 60 rpm, vacuum degree −0.098 MPa) to obtain a 48% lithium chloride solution (i.e., rotary evaporation liquid);
[0048] (4) placing the rotary evaporation liquid obtained in step (3) into a vacuum drying oven for vacuum drying (vacuum temperature 110° C., time 7 h, vacuum degree -0.098 MPa) to obtain crude lithium chloride;
[0049] (5) mixing the crude lithium chloride obtained in step (4) and ammonium bifluoride in a molar ratio of 1:1.3, and reacting at 160° C. for 3 h under a 99.999% nitrogen atmosphere;
[0050] (6) Finally, the temperature was raised to 420° C. in a 99.999% nitrogen atmosphere for reaction for 3 h to obtain 24.93 g of the battery-grade lithium fluoride.
[0051] The product yield is 97.02%, and the measured product purity is 99.96%. The impurities sodium is 5ppm, magnesium is 4ppm, potassium is 5ppm, calcium is 6ppm, iron is 5ppm, and sulfate is 12ppm, which can meet the battery grade lithium fluoride standard.
[0052] Example 3
[0053] Take industrial-grade lithium chloride raw material and set it aside; the content of the raw industrial-grade lithium chloride is 99.08%, sodium is 146ppm, magnesium is 20ppm, potassium is 155ppm, calcium is 67ppm, iron is 11ppm, and sulfate is 77ppm.
[0054] A method for preparing battery-grade lithium fluoride by a solid phase method comprises the following steps:
[0055] (1) Pour a mixed extractant obtained by mixing di(2-ethylhexyl) phosphate (P204) and sulfonated kerosene at a ratio of 60 mL:40 mL into a separatory funnel, then add 8 mL of a 12.5 wt% NaOH solution to the separatory funnel until the pH value is 11, then shake for 8 minutes, let stand, separate and remove the lower aqueous phase to obtain an extract;
[0056] (2) Pour 141.3 g of 30% lithium chloride solution into the extract obtained in step (1) to extract and remove impurities, and retain the lower layer liquid;
[0057] (3) subjecting the lower layer liquid obtained in step (2) to rotary evaporation (rotary evaporation temperature: 90° C., rotation speed: 70 rpm, vacuum degree: −0.098 MPa) to obtain a 54% lithium chloride solution (i.e., rotary evaporation liquid);
[0058] (4) placing the rotary evaporation liquid obtained in step (3) into a vacuum drying oven for vacuum drying (vacuum temperature 130° C., time 8 h, vacuum degree -0.098 MPa) to obtain crude lithium chloride;
[0059] (5) mixing the crude lithium chloride obtained in step (4) and ammonium bifluoride in a molar ratio of 1:1.4, and reacting at 170° C. for 4 h under a 99.999% nitrogen atmosphere;
[0060] (6) Finally, the temperature was raised to 500° C. in a 99.999% nitrogen atmosphere for reaction for 4 h to obtain 24.91 g of the battery-grade lithium fluoride.
[0061] The product yield is 96.94%, and the measured product purity is 99.96%. The impurities sodium is 2ppm, magnesium is 2ppm, potassium is 4ppm, calcium is 3ppm, iron is 5ppm, and sulfate is 13ppm, which can meet the battery grade lithium fluoride standard.
[0062] Example 4
[0063] Take industrial-grade lithium chloride raw material and set it aside; the content of the raw industrial-grade lithium chloride is 99.05%, sodium is 185ppm, magnesium is 18ppm, potassium is 124ppm, calcium is 66ppm, iron is 11ppm, and sulfate is 73ppm.
[0064] A method for preparing battery-grade lithium fluoride by a solid phase method comprises the following steps:
[0065] (1) Pour the mixed extractant obtained by mixing di(2-ethylhexyl) phosphate (P204) and sulfonated kerosene at a ratio of 80 mL:20 mL into a separatory funnel, then add 10 mL of 10 wt% NaOH solution to the separatory funnel until the pH value is 12, then shake for 10 minutes, let stand and separate the lower aqueous phase to obtain an extract;
[0066] (2) Pour 423.9 g of 10% lithium chloride solution into the extract obtained in step (1) to extract and remove impurities, and retain the lower layer liquid;
[0067] (3) subjecting the lower layer liquid obtained in step (2) to rotary evaporation (rotary evaporation temperature: 70° C., rotation speed: 50 rpm, vacuum degree: −0.098 MPa) to obtain a 60% lithium chloride solution (i.e., rotary evaporation liquid);
[0068] (4) placing the rotary evaporation liquid obtained in step (3) into a vacuum drying oven for vacuum drying (vacuum temperature 140° C., time 10 h, vacuum degree −0.098 MPa) to obtain crude lithium chloride;
[0069] (5) mixing the crude lithium chloride obtained in step (4) and ammonium bifluoride in a molar ratio of 1:1.4, and reacting at 180° C. for 6 h under a 99.999% nitrogen atmosphere;
[0070] (6) Finally, the temperature was raised to 600° C. in a 99.999% nitrogen atmosphere for reaction for 5 h to obtain 24.92 g of the battery-grade lithium fluoride.
[0071] The product yield is 96.98%, and the measured product purity is 99.96%. The impurities sodium is 3ppm, magnesium is 5ppm, potassium is 2ppm, calcium is 2ppm, iron is 6ppm, and sulfate is 12ppm, which can meet the battery grade lithium fluoride standard.
[0072] Example 5
[0073] Take industrial-grade lithium chloride raw material and set it aside; the content of the raw industrial-grade lithium chloride is 99.12%, sodium is 167ppm, magnesium is 22ppm, potassium is 175ppm, calcium is 61ppm, iron is 12ppm, and sulfate is 85pm.
[0074] A method for preparing battery-grade lithium fluoride by a solid phase method comprises the following steps:
[0075] (1) Pour a mixed extractant obtained by mixing di(2-ethylhexyl) phosphate (P204) and sulfonated kerosene at a ratio of 20 mL:80 mL into a separatory funnel, then add 10 mL of a 10 wt% NaOH solution to the separatory funnel until the pH value is 11, then shake for 3 minutes, let stand and separate the lower aqueous phase to obtain an extract;
[0076] (2) Pour 211.95 g of 20% lithium chloride solution into the extract obtained in step (1) to extract and remove impurities, and retain the lower layer liquid;
[0077] (3) subjecting the lower layer liquid obtained in step (2) to rotary evaporation (rotary evaporation temperature 80° C., rotation speed 60 rpm, vacuum degree −0.098 MPa) to obtain a 42% lithium chloride solution (i.e., rotary evaporation liquid);
[0078] (4) placing the rotary evaporation liquid obtained in step (3) into a vacuum drying oven for vacuum drying (vacuum temperature 100° C., time 5 h, vacuum degree -0.098 MPa) to obtain crude lithium chloride;
[0079] (5) mixing the crude lithium chloride obtained in step (4) and ammonium bifluoride in a molar ratio of 1:1.2, and reacting at 160° C. for 3 h under a 99.999% argon atmosphere;
[0080] (6) Finally, the temperature was raised to 350° C. in a 99.999% argon atmosphere for reaction for 3 h to obtain 24.92 g of the battery-grade lithium fluoride.
[0081] The product yield is 96.98%, and the measured product purity is 99.96%. The impurities sodium is 4ppm, magnesium is 3ppm, potassium is 6ppm, calcium is 5ppm, iron is 4ppm, and sulfate is 8ppm, which can meet the battery grade lithium fluoride standard.
[0082] Example 6
[0083] Take industrial-grade lithium chloride raw material and set it aside; the content of the raw industrial-grade lithium chloride is 99.05%, sodium is 128ppm, magnesium is 19ppm, potassium is 168ppm, calcium is 59ppm, iron is 13ppm, and sulfate is 66ppm.
[0084] A method for preparing battery-grade lithium fluoride by a solid phase method comprises the following steps:
[0085] (1) Pour a mixed extractant obtained by mixing di(2-ethylhexyl) phosphate (P204) and sulfonated kerosene at a ratio of 40 mL:60 mL into a separatory funnel, then add 5 mL of a 20 wt% NaOH solution to the separatory funnel until the pH value is 10, then shake for 5 minutes, let stand, separate and remove the lower aqueous phase to obtain an extract;
[0086] (2) Pour 141.3 g of 30% lithium chloride solution into the extract obtained in step (1) to extract and remove impurities, and retain the lower layer liquid;
[0087] (3) subjecting the lower layer liquid obtained in step (2) to rotary evaporation (rotary evaporation temperature: 90° C., rotation speed: 70 rpm, vacuum degree: −0.098 MPa) to obtain a 48% lithium chloride solution (i.e., rotary evaporation liquid);
[0088] (4) placing the rotary evaporation liquid obtained in step (3) into a vacuum drying oven for vacuum drying (vacuum temperature 120° C., time 7 h, vacuum degree -0.098 MPa) to obtain crude lithium chloride;
[0089] (5) mixing the crude lithium chloride obtained in step (4) and ammonium bifluoride in a molar ratio of 1:1.3, and reacting at 160° C. for 3 h under a 99.999% argon atmosphere;
[0090] (6) Finally, the temperature was raised to 420° C. in a 99.999% argon atmosphere for reaction for 3 h to obtain 24.95 g of the battery-grade lithium fluoride.
[0091] The product yield is 97.10%, and the measured product purity is 99.96%. The impurities sodium is 3ppm, magnesium is 4ppm, potassium is 4ppm, calcium is 4ppm, iron is 2ppm, and sulfate is 12ppm, which can meet the battery grade lithium fluoride standard.
[0092] Example 7
[0093] Take industrial-grade lithium chloride raw material and set it aside; the content of the raw industrial-grade lithium chloride is 99.07%, sodium is 177ppm, magnesium is 21ppm, potassium is 185ppm, calcium is 55ppm, iron is 13ppm, and sulfate is 66pm.
[0094] A method for preparing battery-grade lithium fluoride by a solid phase method comprises the following steps:
[0095] (1) Pour a mixed extractant obtained by mixing di(2-ethylhexyl) phosphate (P204) and sulfonated kerosene at a ratio of 60 mL:40 mL into a separatory funnel, then add 8 mL of a 12.5 wt% NaOH solution to the separatory funnel until the pH value is 11, then shake for 8 minutes, let stand, separate and remove the lower aqueous phase to obtain an extract;
[0096] (2) Pour 423.9 g of 10% lithium chloride solution into the extract obtained in step (1) to extract and remove impurities, and retain the lower layer liquid;
[0097] (3) subjecting the lower layer liquid obtained in step (2) to rotary evaporation (rotary evaporation temperature: 70° C., rotation speed: 50 rpm, vacuum degree: −0.098 MPa) to obtain a 54% lithium chloride solution (i.e., rotary evaporation liquid);
[0098] (4) placing the rotary evaporation liquid obtained in step (3) into a vacuum drying oven for vacuum drying (vacuum temperature 130° C., time 8 h, vacuum degree -0.098 MPa) to obtain crude lithium chloride;
[0099] (5) mixing the crude lithium chloride obtained in step (4) and ammonium bifluoride in a molar ratio of 1:1.4, and reacting at 170° C. for 4 h under a 99.999% argon atmosphere;
[0100] (6) Finally, the temperature was raised to 500° C. in a 99.999% argon atmosphere for 4 h to obtain 24.91 g of the battery-grade lithium fluoride.
[0101] The product yield is 96.94%, and the measured product purity is 99.96%. The impurities sodium is 5ppm, magnesium is 6ppm, potassium is 3ppm, calcium is 3ppm, iron is 5ppm, and sulfate is 14ppm, which can meet the battery grade lithium fluoride standard.
[0102] Example 8
[0103] Take industrial-grade lithium chloride raw material and set it aside; the content of the raw industrial-grade lithium chloride is 99.07%, sodium is 182ppm, magnesium is 41ppm, potassium is 175ppm, calcium is 57ppm, iron is 11ppm, and sulfate is 58ppm.
[0104] A method for preparing battery-grade lithium fluoride by a solid phase method comprises the following steps:
[0105] (1) Pour the mixed extractant obtained by mixing di(2-ethylhexyl) phosphate (P204) and sulfonated kerosene at a ratio of 80 mL:20 mL into a separatory funnel, then add 10 mL of 10 wt% NaOH solution to the separatory funnel until the pH value is 12, then shake for 10 minutes, let stand and separate the lower aqueous phase to obtain an extract;
[0106] (2) Pour 211.95 g of 20% lithium chloride solution into the extract obtained in step (1) to extract and remove impurities, and retain the lower layer liquid;
[0107] (3) subjecting the lower layer liquid obtained in step (2) to rotary evaporation (rotary evaporation temperature 80° C., rotation speed 60 rpm, vacuum degree −0.098 MPa) to obtain a 60% lithium chloride solution (i.e., rotary evaporation liquid);
[0108] (4) placing the rotary evaporation liquid obtained in step (3) into a vacuum drying oven for vacuum drying (vacuum temperature 140° C., time 10 h, vacuum degree −0.098 MPa) to obtain crude lithium chloride;
[0109] (5) mixing the crude lithium chloride obtained in step (4) and ammonium bifluoride in a molar ratio of 1:1.5, and reacting at 180° C. for 6 h under a 99.999% nitrogen atmosphere;
[0110] (6) Finally, the temperature was raised to 500° C. in a 99.999% nitrogen atmosphere for reaction for 5 h to obtain 24.91 g of the battery-grade lithium fluoride.
[0111] The product yield is 96.94%, and the measured product purity is 99.96%. The impurities sodium is 6ppm, magnesium is 2ppm, potassium is 4ppm, calcium is 2ppm, iron is 3ppm, and sulfate is 9ppm, which can meet the battery grade lithium fluoride standard.
[0112] Comparative Example 1
[0113] Take industrial-grade lithium chloride raw material and set it aside; the content of the raw industrial-grade lithium chloride is 99.06%, sodium is 168ppm, magnesium is 22ppm, potassium is 167ppm, calcium is 70ppm, iron is 12ppm, and sulfate is 95ppm.
[0114] A method for preparing lithium fluoride by a solid phase method comprises the following steps:
[0115] (1) Pour 100 mL of di(2-ethylhexyl) phosphate (P204) into a separatory funnel, then add 10 mL of 10 wt% NaOH solution to the separatory funnel until the pH value is 11, then shake for 3 minutes, let stand and remove the lower aqueous phase to obtain an extract;
[0116] (2) Pour 423.9 g of 10% lithium chloride solution into the extract obtained in step (1) to extract and remove impurities, and retain the lower layer liquid;
[0117] (3) subjecting the lower layer liquid obtained in step (2) to rotary evaporation (rotary evaporation temperature: 70° C., rotation speed: 50 rpm, vacuum degree: −0.098 MPa) to obtain a 42% lithium chloride solution (i.e., rotary evaporation liquid);
[0118] (4) placing the rotary evaporation liquid obtained in step (3) into a vacuum drying oven for vacuum drying (vacuum temperature 100° C., time 5 h, vacuum degree -0.098 MPa) to obtain crude lithium chloride;
[0119] (5) mixing the crude lithium chloride obtained in step (4) and ammonium bifluoride in a molar ratio of 1:1.2, and reacting at 160° C. for 3 h under a 99.999% argon atmosphere;
[0120] (6) Finally, the temperature was raised to 350° C. under a 99.999% argon atmosphere for reaction for 3 h to obtain 23.82 g of lithium fluoride.
[0121] The product yield was 92.70%, and the measured product purity was 99.82%. The impurities sodium was 62 ppm, magnesium was 5 ppm, potassium was 160 ppm, calcium was 6 ppm, iron was 10 ppm, and sulfate was 14 ppm, which did not meet the battery-grade lithium fluoride standard.
[0122] Comparative Example 2
[0123] Take industrial-grade lithium chloride raw material and set it aside; the content of the raw industrial-grade lithium chloride is 99.06%, sodium is 168ppm, magnesium is 22ppm, potassium is 167ppm, calcium is 70ppm, iron is 12ppm, and sulfate is 95ppm.
[0124] A method for preparing lithium fluoride by a solid phase method comprises the following steps:
[0125] (1) Pour 100 mL of sulfonated kerosene into a separatory funnel, then add 10 mL of 10 wt% NaOH solution to the separatory funnel until the pH value is 11, then shake for 3 min, let stand and remove the lower aqueous phase to obtain an extract;
[0126] (2) Pour 423.9 g of 10% lithium chloride solution into the extract obtained in step (1) to extract and remove impurities, and retain the lower layer liquid;
[0127] (3) subjecting the lower layer liquid obtained in step (2) to rotary evaporation (rotary evaporation temperature: 70° C., rotation speed: 50 rpm, vacuum degree: −0.098 MPa) to obtain a 42% lithium chloride solution (i.e., rotary evaporation liquid);
[0128] (4) placing the rotary evaporation liquid obtained in step (3) into a vacuum drying oven for vacuum drying (vacuum temperature 100° C., time 5 h, vacuum degree -0.098 MPa) to obtain crude lithium chloride;
[0129] (5) mixing the crude lithium chloride obtained in step (4) and ammonium bifluoride in a molar ratio of 1:1.2, and reacting at 160° C. for 3 h under a 99.999% argon atmosphere;
[0130] (6) Finally, the temperature was raised to 350° C. under a 99.999% argon atmosphere for reaction for 3 h to obtain 23.77 g of lithium fluoride.
[0131] The product yield was 92.51%, and the measured product purity was 99.91%. The impurities sodium was 58 ppm, magnesium was 20 ppm, potassium was 6 ppm, calcium was 68 ppm, iron was 10 ppm, and sulfate was 14 ppm, which did not meet the battery-grade lithium fluoride standard.
[0132] Comparative Example 3
[0133] Take industrial-grade lithium chloride raw material and set it aside; the content of the raw industrial-grade lithium chloride is 99.06%, sodium is 168ppm, magnesium is 22ppm, potassium is 167ppm, calcium is 70ppm, iron is 12ppm, and sulfate is 95ppm.
[0134] A method for preparing lithium fluoride by a solid phase method comprises the following steps:
[0135] (1) Add 10 mL of 10 wt% NaOH solution to a separatory funnel until the pH value is 11, then shake for 3 min, let stand and separate the lower aqueous phase to obtain an extract;
[0136] (2) Pour 423.9 g of 10% lithium chloride solution into the extract obtained in step (1) to extract and remove impurities, and retain the lower layer liquid;
[0137] (3) subjecting the lower layer liquid obtained in step (2) to rotary evaporation (rotary evaporation temperature: 70° C., rotation speed: 50 rpm, vacuum degree: −0.098 MPa) to obtain a 42% lithium chloride solution (i.e., rotary evaporation liquid);
[0138] (4) placing the rotary evaporation liquid obtained in step (3) into a vacuum drying oven for vacuum drying (vacuum temperature 100° C., time 5 h, vacuum degree -0.098 MPa) to obtain crude lithium chloride;
[0139] (5) mixing the crude lithium chloride obtained in step (4) and ammonium bifluoride in a molar ratio of 1:1.2, and reacting at 160° C. for 3 h under a 99.999% argon atmosphere;
[0140] (6) Finally, the temperature was raised to 350° C. under a 99.999% argon atmosphere for reaction for 3 h to obtain 22.44 g of lithium fluoride.
[0141] The product yield was 87.33%, and the measured product purity was 99.86%. The impurities sodium was 157 ppm, magnesium was 20 ppm, potassium was 164 ppm, calcium was 68 ppm, iron was 12 ppm, and sulfate was 89 ppm, which did not meet the battery-grade lithium fluoride standard.
[0142] The applicant declares that the present invention illustrates the technical solution of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of individual raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing battery-grade lithium fluoride by a solid phase method, characterized in that: The steps include: (1) pouring a mixed extractant obtained by mixing di(2-ethylhexyl) phosphate and sulfonated kerosene into a funnel, adjusting the pH value, shaking, separating the layers, and removing the lower aqueous phase to obtain an extract; (2) pouring the lithium chloride solution into the extract obtained in step (1) to extract and remove impurities, and retaining the lower layer liquid; (3) subjecting the lower layer liquid obtained in step (2) to rotary evaporation to obtain a rotary evaporation liquid; (4) vacuum drying the rotary evaporation liquid obtained in step (3) to obtain crude lithium chloride; (5) mixing the crude lithium chloride obtained in step (4) and ammonium bifluoride, and then reacting; (6) Raise the temperature and remove impurities to obtain battery-grade lithium fluoride.
2. The method for preparing battery-grade lithium fluoride by a solid phase method according to claim 1, characterized in that: In step (1), the volume ratio of di(2-ethylhexyl)phosphate to sulfonated kerosene is 2-8:2-8.
3. The method for preparing battery-grade lithium fluoride by a solid phase method according to claim 1, characterized in that: In step (1), the pH value is adjusted to 10-12; a 5-10 wt % sodium hydroxide solution is used to adjust the pH value; and the oscillation time is 3-10 min.
4. The method for preparing battery-grade lithium fluoride by a solid phase method according to claim 1, characterized in that: In step (2), the concentration of the lithium chloride solution is 10 to 30 wt%.
5. The method for preparing battery-grade lithium fluoride by a solid phase method according to claim 1, characterized in that: In step (3), the rotary evaporation temperature is 70 to 90° C., the rotation speed is 50 to 70 rpm, and the vacuum degree is -0.05 to -0.1 MPa; The concentration of the rotary evaporation liquid is 40-60wt%.
6. The method for preparing battery-grade lithium fluoride by a solid phase method according to claim 1, characterized in that: In step (4), the vacuum drying temperature is 100 to 140° C., the drying time is 5 to 10 hours, and the vacuum degree is -0.05 to -0.1 MPa.
7. The method for preparing battery-grade lithium fluoride by a solid phase method according to claim 1, characterized in that: In step (5), the molar ratio of crude lithium chloride to ammonium bifluoride is 1:1.2-1.
5.
8. The method for preparing battery-grade lithium fluoride by a solid phase method according to claim 1, characterized in that: In step (5), the reaction is carried out under an argon or nitrogen atmosphere, the reaction temperature is 160-180° C., and the reaction time is 3-5 h.
9. The method for preparing battery-grade lithium fluoride by a solid phase method according to claim 1, characterized in that: In step (6), the temperature is increased to remove impurities under an argon or nitrogen atmosphere, the temperature is 350 to 600° C., and the insulation time is 3 to 5 hours.
10. Battery-grade lithium fluoride prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Method for preparing nano lithium fluoride by utilizing solid-phase reaction
CN115304084A
Technology for separating alkaline earth metal impurities in lithium chloride by employing quasi fractional distillation extraction method
CN103738982A
Method for removing calcium and magnesium impurities in lithium-rich solution by extraction process
CN105712383A
Extraction system and extraction method for extracting lithium from chloride type salt lake brine
CN117512357A
Preparation method of high-purity nano aluminium fluoride
CN1962445A